Central bank losses and monetary policy rules: A DSGE investigation - Jonathan Benchimol; André Fourçans (International Review of Economics & Finance, 2019)
Central banks' monetary policy rules being consistent with policy objectives are a fundamental of applied monetary economics. We seek to determine, first, which of the central bank's rules are most in line with the historical data for the US economy and, second, what policy rule would work best to assist the central bank in reaching its objectives via several loss function measures. We use Bayesian estimations to evaluate twelve monetary policy rules from 1955 to 2017 and over three different sub-periods. We find that when considering the central bank's loss functions, the estimates often indicate the superiority of NGDP level targeting rules, though Taylor-type rules lead to nearly identical implications. However, the results suggest that various central bank empirical rules, be they NGDP or Taylor type, are more appropriate to achieve the central bank's objectives for each type of period (stable, crisis, recovery).
Keywords: E52; E58; E32; C11; C61; 330; Monetary policy; Monetary rule; Central bank loss; Central banking; Federal Reserve; DSGE models